WASTE MANAGEMENT IN THE FOOD INDUSTRY - Mendes Baptista, João Lucas; Rodolpho, Daniela (Revista Interface Tecnológica, 2021)
Currently the food scenery is essential for the country’s economy, being the sector that grows the most, which consequently also ends up being the one that the most generates solid or effluent waste, which owe have a correct destination and in accordance with the legislation in force in the country. . Therefore, it is in this context that this article intends to show through bibliographic research, quantitative research and online research, that waste in the food industry, if not treated correctly, can cause great losses for the company not only in the economic ambit but also in the âmbit social as the consumer is aware of the way in which these companies destining of their waste.